2018
DOI: 10.1128/msystems.00205-17
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Host MicroRNAs and the Gut Microbiota in Colorectal Cancer

Abstract: Recent studies have found an association between colorectal cancer (CRC) and the gut microbiota. One potential mechanism by which the microbiota can influence host physiology is through affecting gene expression in host cells. MicroRNAs (miRNAs) are small noncoding RNA molecules that can regulate gene expression and have important roles in cancer development. Here, we investigated the link between the gut microbiota and the expression of miRNA in CRC. We found that dozens of miRNAs are differentially regulated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 88 publications
(110 reference statements)
2
100
0
Order By: Relevance
“…CRC is an evolving disease, characterized by a series of molecular and microbial changes (14)(15)(16), suggesting a dynamic interplay between the host and intestinal microbiota as the disease progresses. MicroRNAs (miRNAs) have emerged as potential mediators of these host-microbe interactions with their ability to modulate both host (17) and bacterial genes, which can result in shifts in microbiota composition (18,19). In turn, the microbiota is able to modulate host miRNA expression (18,20,21), with F. nucleatum targeting several miRNAs related to CRC pathogenesis (5,22).…”
mentioning
confidence: 99%
“…CRC is an evolving disease, characterized by a series of molecular and microbial changes (14)(15)(16), suggesting a dynamic interplay between the host and intestinal microbiota as the disease progresses. MicroRNAs (miRNAs) have emerged as potential mediators of these host-microbe interactions with their ability to modulate both host (17) and bacterial genes, which can result in shifts in microbiota composition (18,19). In turn, the microbiota is able to modulate host miRNA expression (18,20,21), with F. nucleatum targeting several miRNAs related to CRC pathogenesis (5,22).…”
mentioning
confidence: 99%
“…Similar to previous reports in humans, we found variations to the microbiota composition between different NHP subjects. Previous studies suggest that this variation between individuals can be attributed to factors such as genetics, dietary preferences and other factors [1,32,33]. We found that both small and large intestinal tissues have significant interindividual variations, although the statistical significance in the small intestinal tissues is more pronounced compared to the large intestines (PERMANOVA, P < 9.999e-05 vs. P < 0.05).…”
Section: Discussionmentioning
confidence: 40%
“…The human gastrointestinal (GI) tract harbors trillions of microorganisms, including thousands of bacterial species, termed the microbiota [1]. It has become evident that the gut microbiota is important in regulating and maintaining the health of the host and is implicated in many diseases, such as cancers [1][2][3][4][5]. Despite numerous studies indicating important roles of microbiota in diseases, many of these studies have largely focused on the taxonomic composition of the microbiota [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have shown that the microbiome can affect gene regulation in interacting host cells, [43][44][45] and in particular in colonic tumors. 46 In addition, the effects of immune elements, tumor heterogeneity, epigenetic factors, and the developmental history of the tissue may also be important for interaction with the microbiome. 47 It is also likely that the viral community present in the gut plays an important role, interacting with both host and microbial cells.…”
Section: Next Steps and Open Questionsmentioning
confidence: 99%